Discovery of a chemosynthesis-based community in the western South Atlantic Ocean. (June 2016) - Giongo, Adriana; Haag, Taiana; Simão, Taiz L. Lopes; Medina-Silva, Renata; Utz, Laura R.P.; Bogo, Maurício R.; Bonatto, Sandro L.; Zamberlan, Priscilla M.; Augustin, Adolpho H.; Lourega, Rogério V.; Rodrigues, Luiz F.; Sbrissa, Gesiane F.; et al.
Abstract: Chemosynthetic communities have been described from a variety of deep-sea environments across the world's oceans. They constitute very interesting biological systems in terms of their ecology, evolution and biogeography, and also given their potential as indicators of the presence and abundance of consistent hydrocarbon-based nutritional sources. Up to now such peculiar biotic assemblages have not been reported for the western South Atlantic Ocean, leaving this large region undocumented with respect to the presence, composition and history of such communities. Here we report on the presence of a chemosynthetic community off the coast of southern Brazil, in an area where high-levels of methane and the presence of gas hydrates have been detected. We performed metagenomic analyses of the microbial community present at this site, and also employed molecular approaches to identify components of its benthic fauna. We conducted phylogenetic analyses comparing the components of this assemblage to those found elsewhere in the world, which allowed a historical assessment of the structure and dynamics of these systems. Our results revealed that the microbial community at this site is quite diverse, and contains many components that are very closely related to lineages previously sampled in ecologically similar environments across the globe. Anaerobic methanotrophic (ANME) archaeal groups were found to be very abundant at this site, suggesting that methane is indeed an important source of nutrition for this community. In addition, we document the presence at this site of a vestimentiferan siboglinid polychaete and the bivalve Acharax sp., both of which are typical components of deep-sea chemosynthetic communities. The remarkable similarity in biotic composition between this area and other deep-sea communities across the world supports the interpretation that these assemblages are historically connected across the global oceans, undergoing colonization from distant sites and influenced by local ecological features that select a stereotyped suite of specifically adapted organisms. Highlights: We identified a chemosynthesis-based community in the Western South Atlantic Ocean. We characterized microbial and metazoan components of the community. Organisms from this site are closely related to members of geographically distant communities. Our results support world-wide historical connectivity among such biotic assemblages.